The Effect of Natural Resource Profit Sharing Funds and Investment on Regional Gross Domestic Product through Regional Expenditure in Kutai Timur Regency - Diana Lestari; Siti Amalia; Nurjanana Nurjanana; Suhartini Suhartini (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the effect of Natural Resource Profit Sharing Funds (DBH SDA) and investment on Gross Regional Domestic Product (GRDP) through regional expenditure in Kutai Timur Regency. The research employs path analysis with a multiple linear regression model using time series data from 2013-2022. The results indicate that DBH SDA has a significant positive effect on regional expenditure but a significant negative effect on GRDP. Conversely, investment has an insignificant negative effect on regional expenditure but a significant positive effect on GRDP. Furthermore, regional expenditure significantly and positively influences GRDP. Additional analysis reveals that the impact of DBH SDA on GRDP is more substantial through regional expenditure, while the direct effect of investment on GRDP is more pronounced. This study highlights the importance of efficient DBH SDA management and the optimization of investments to support regional economic growth.